SISTEM INFORMASI KEUANGAN MENGGUNAKANDYNAMIC SYSTEM DEVELOPMENT METHOD PADAUMKM BUTONG RECIPE - Rachel Maria Susana, (2022)
In this pandemic situation, a lot of people in Indonesia starting their small business and it called UMKM or micro, small, medium business. UMKM itself needs an activity to take notes on their financial, their capital venture and financial recapitulation. Because all of those activities, a study case was taken to UMKM Butong Recipe. In the year 2020, this UMKM sold over 330 orders. And also in the year of 2021, from the early year until September, this UMKM had sold over 683 orders. With that amount of orders, its directly proportional with the income of the UMKM. There for, it can be concluded that the income was increasing in such a good way, and because of it, this UMKM needed a computerized system to take notes or to process their financial situations. Because this UMKM still using an accountant book to manually processing their financial situations. Based on this situations, a computerized financial information system was made using Dynamic System Development Method (DSDM), so this system can make a result precisely according what the user want. For conclusion, this UMKM can have a financial system to support their business.